Covoiturage au Grand-Nokoué et plateformes numériques de mobilité partagée en Afrique de l'Ouest - Raynald Ballo (Netcom)
Shared mobilities, particularly carpooling, foster a paradox in Africa. While bush taxis have experienced historic success for the past 50 years due to traditional sharing practices transposed into public transport, modernization through digital platforms is struggling to take root in a sustainable way. This observation, highlighted through maps, underscores the recurring failures of initiatives taken in West Africa. Indeed, over the past 15 years, more than half of the companies created in this sector have been abandoned. In Grand-Nokoué, Benin, a qualitative and quantitative survey of 230 users combined with a documentary analysis at the West African level, makes it possible to understand their difficulties. Data from an immersion in the field reveals three major factors: a more flexible relationship to time without a culture of rigorous planning, out of step with the rational logic of platforms; a deeply rooted community conception of travel based on social proximity, contrary to sharing with strangers; a sense of insecurity towards outsiders and a primacy of individual comfort, contrary to the spirit of carpooling. The working classes, versed in ancestral practices of mutual aid in transport, could play a key role in the sustainable territorial anchoring of the new services. However, innovative initiatives in the field of platforms require strong political support, which is not yet acquired here, and, concurrently, a "progressive" familiarization that is still very much in progress.